Experiences of the SARS-CoV-2 pandemic amongst Australian healthcare workers: from stressors to protective factors. (March 2022) - Broom, J.; Williams Veazey, L.; Broom, A.; Hor, S.; Degeling, C.; Burns, P.; Wyer, M.; Gilbert, G.L.
Summary: Background: The SARS-CoV-2 pandemic has critically challenged healthcare systems globally. Examining the experiences of healthcare workers (HCWs) is important for optimizing ongoing and future pandemic responses. Objectives: In-depth exploration of Australian HCWs' experiences of the SARS-CoV-2 pandemic, with a focus on reported stressors vis-à-vis protective factors. Methods: Individual interviews were performed with 63 HCWs in Australia. A range of professional streams and operational staff were included. Thematic analysis was performed. Results: Thematic analysis identified stressors centred on paucity of, or changing, evidence, leading to absence of, or mistrust in, guidelines; unprecedented alterations to the autonomy and sense of control of clinicians; and deficiencies in communication and support. Key protective factors included: the development of clear guidance from respected clinical leaders or recognized clinical bodies, interpersonal support, and strong teamwork, leadership, and a sense of organizational preparedness. Conclusions: This study provides insights into the key organizational sources of emotional stress for HCWs within pandemic responses and describes experiences of protective factors. HCWs experiencing unprecedented uncertainty, fear, and rapid change, rely on clear communication, strong leadership, guidelines endorsed by recognized expert groups or individuals, and have increased reliance on interpersonal support. Structured strategies for leadership and communication at team, service group and organizational levels, provision of psychological support, and consideration of the potential negative effects of centralizing control, would assist in ameliorating the extreme pressures of working within a pandemic environment.